Repetitive Daily Blindness with Hemiplegic Migraine and SCN1A Mutations - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Two novel SCN1A mutations are identified in two unrelated families with familial hemiplegic migraine and a unique phenotype of elicited repetitive daily blindness, in a report from Hopital Lariboisiere, and other centers in Paris, France, and Geneva, Switzerland.